2020
DOI: 10.32553/ijmbs.v4i9.1411
|View full text |Cite
|
Sign up to set email alerts
|

Study of Menstrual Practices in India – Acquaintance With Menstrual Cups

Abstract: Background: All those who menstruate need the awareness and access to their choice of menstrual materials that are safe, comfortable and support sustainable production and use. It is necessary to address menstruation to understand the need to take subsequent steps for a woman who menstruates for a period of 40 years of her life. Method: A cross-sectional, standardized questionnaire based survey method was used to collect information from a sample size of 500 people after prior institutional ethical clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Literature shows few studies from India reported on the awareness and usage of menstrual cups. [12][13][14][15][16][17] In a study done among South Indian gynaecologists in 2019, only 26.5% were found to be aware of menstrual cup. 12 Lack of awareness about menstrual cups was also observed among medical students in Bangalore.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature shows few studies from India reported on the awareness and usage of menstrual cups. [12][13][14][15][16][17] In a study done among South Indian gynaecologists in 2019, only 26.5% were found to be aware of menstrual cup. 12 Lack of awareness about menstrual cups was also observed among medical students in Bangalore.…”
Section: Introductionmentioning
confidence: 99%
“…13 India being a conservative country, insertion of a penetrating device into the vagina of a woman is considered disgusting. 15 Moreover, irrespective of educational status there is a notion that inserting a vaginal cup will lead to loss of virginity. 15 However, insertion and removal became easy with subsequent menstrual cycles and comfort level increased with experience in 90% of married women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation